Pengaruh e-satisfaction terhadap repurchase intention produk fashion dimediasi oleh electronic word of mouth (E-WOM) - Koerniawan Hidajat; Widia Damayanti (MBR (Management and Business Review), 2022)
This study aims to determine and explain the effect of e-satisfaction on repurchase intention mediated by electronic word of mouth (E-WOM) in the millennial generation of Shopee marketplace users in DKI Jakarta. This research method is quantitative explanatory. The sampling technique was purposive sampling, with 105 respondents. And online surveys using Google Forms and the Likert Scale. SPSS 22, AMOS V22 and Zsobel test data processing tests. The results of the study reveal that e-satisfaction affects repurchase intention, besides that it also influences electronic word of mouth (E-WOM), then electronic word of mouth (E-WOM) influences repurchase intention. Another finding is that electronic word of mouth (E-WOM) mediates the effect of e-satisfaction on repurchase intention in the millennial generation of market users place Shopee in DKI Jakarta.